Acute enteral manganese intoxication with hepatic failure due to ingestion of a joint supplement overdose. (September 2014) - Borchers, Angela; Epstein, Steven E.; Gindiciosi, Blaz; Cartoceti, Andrew; Puschner, Birgit
Manganese is a ubiquitous, essential trace element and a common ingredient of joint supplement tablets. Little information is known about the inherent toxic potential if ingested at higher doses. A 5-year-old female spayed Pug dog presented for evaluation of vomiting and ataxia after accidental ingestion of approximately 100 joint supplement tablets. The dog developed acute hepatic failure and was euthanized 6 days after presentation due to progression of the disease. Necropsy showed severe acute hepatic necrosis. Liver and kidney samples were submitted for toxicology analysis, results of which showed severely elevated manganese concentrations in the liver and kidneys.